A nitrogen-doped graphene electrocatalyst for selective oxygen reduction in presence of glucose and D-gluconic acid in pH-neutral media. (20th December 2015) - Qazzazie, Dureid; Beckert, Michaela; Mülhaupt, Rolf; Yurchenko, Olena; Urban, Gerald
Abstract: The development of high-active, selective and low-cost electrocatalysts for oxygen reduction reaction (ORR) is of major interest for catalysis in fuel cells. In this article, we present various nitrogen-doped graphenes as high performance non-metal electrocatalysts for ORR based on graphene thermally treated with cyanamide. The impact of treatment temperature on the structure and ORR performance of prepared samples is systematically investigated. Obtained results indicate that electrochemically active surface area (ECSA) and electrocatalytic ORR activity at both neutral and alkaline conditions are enhanced for samples treated at higher temperatures showing a clear correlation between ECSA and ORR activity. A comparison of determined ORR performances with XPS results demonstrates that not the total quantity of nitrogen improves ORR activity, but we think that optimum content of graphitic nitrogen functionality is mainly responsible for the improved electrocatalytic performance. The main novelties of our work are specifically the voltammetric studies of the ORR mechanism on prepared nitrogen-doped graphene and the investigation of the electrocatalytic activity in presence of glucose and D-gluconic acid in pH-neutral medium. We ascertained superior tolerance of nitrogen-doped graphene towards D-gluconic acid poisoning as well as glucose oxidation. Especially, the sample prepared at 1000 °C exhibits improved electrocatalytic ORR performance compared to graphene-based materials, and significantly enhanced long-term operation stability, D-gluconic acid and glucose tolerance than commercial Pt/C, thus, perfectly suited for use in single-compartment glucose-based fuel cells operating at pH-neutral conditions.